Cyclic Helix B Peptide Prolongs Skin Allograft Survival via Inhibition of B Cell Immune Responses in a Murine Model - Zheng, Long; Wang, Xuanchuan; Hu, Linkun; Gao, Wenjun; Zhang, Weitao; Zhang, Xuepeng; Hu, Chao; Rong, Ruiming; Yang, Cheng; Zhu, Dong (Frontiers in Immunology, 2021)
Antibody-mediated rejection (AMR) represents a major cause of allograft dysfunction and results in allograft failure in solid organ transplantation. Cyclic helix B peptide (CHBP) is a novel erythropoietin-derived peptide that ameliorated renal allograft rejection in a renal transplantation model. However, its effect on AMR remains unknown. This study aimed to investigate the effect of CHBP on AMR using a secondary allogeneic skin transplantation model, which was created by transplanting skin from BALB/c mice to C57BL/6 mice with or without CHBP treatment. A secondary syngeneic skin transplantation model, involving transplantation from C57BL/6 mice to C57BL/6 mice, was also created to act as a control. Skin graft rejection, CD19+ B cell infiltration in the skin allograft, the percentages of splenic plasma cells, germinal center (GC) B cells, and Tfh cells, the serum levels of donor specific antibodies (DSAs), and NF-κB signaling in splenocytes were analyzed. Skin allograft survival was significantly prolonged in the CHBP group compared to the allogeneic group. CHBP treatment also significantly reduced the CD19+ B cell infiltration in the skin allograft, decreased the percentages of splenic plasma cells, GC B cells, and Tfh cells, and ameliorated the increase in the serum DSA level. At a molecular level, CHBP downregulated P100, RelB, and P52 in splenocytes. CHBP prolonged skin allograft survival by inhibiting AMR, which may be mediated by inhibition of NF-κB signaling to suppress B cell immune responses, thereby decreasing the DSA level.